Membuka Gerbang Pengetahuan: Tinjauan Literatur Tentang Implementasi dan Dampak Pembelajaran Terpadu Nested - Sentana, Maria; Septia, Khanza; Septiani, Mawar; Mawaddah, Miftahul; Siregar, Yulia Elfrida Yanti (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research aims to review the literature regarding the implementation and impact of nested integrated education on student learning outcomes. The research method used is a literature review by analyzing various trusted sources such as scientific newspapers, novels and seminar proceedings. Information is analyzed qualitatively by identifying, summarizing, and interpreting data from various sources. The research results show that nested integrated education has proven to be efficient in improving student learning outcomes in various research fields and learning levels. This educational model helps students master concepts in more depth, improve critical thinking skills, and increase learning motivation. In conclusion, nested integrated education is a promising educational model for improving the quality of learning. Implementation of this model needs to be supported by adequate teacher training and the development of quality teaching materials.